THE FUNDAMENTAL RELATIONSHIP OF GREEN ACCOUNTING, CARBON PERFORMANCE, CORPORATE SOCIAL RESPONSIBILITY TO FINANCIAL PERFORMANCE THROUGH ENVIRONMENTAL PERFORMANCE - Neneng Sri Suprihatin; Lulu Nailufaroh; Tania Natasyannisa (UPT Publikasi Ilmiah UNISBA, 2025)
This study examines the effect of green accounting, carbon performance, and corporate social responsibility (CSR) on financial performance, with environmental performance as a mediating variable. A quantitative approach was applied using secondary data from annual and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2022–2024. Data analysis employed multiple regression and mediation testing using SPSS software. The results reveal that green accounting, carbon performance, and CSR significantly affect environmental performance. Furthermore, ecological performance significantly influences financial performance. It also mediates the relationship between the independent variables and financial performance. These findings emphasize the importance of integrating sustainability into corporate strategy to enhance economic value and corporate reputation.